(untitled) (Editora Impacto Científico, 2025)
This article presents part of the results of a research developed within the framework of a Master’s dissertation entitled "Motivation and Continuing Education of Teachers: a multiple case study", carried out in the Municipal Education Networks of Curiúva, Piraí do Sul and Sapopema, in the state of Paraná, Brazil. The objective of this study was to analyze the professional profile of teachers and to understand how motivation affects their participation in continuing education processes. The research adopted a comparative approach and involved the participation of 200 teachers of Early Childhood Education and the first years of Primary Education, through online questionnaires used for data collection, later systematized in graphs and tables. The results show a marked predominance of the female gender, diversity in work ties and variation in the length of teaching experience, as well as a high proportion of teachers with postgraduate studies lato sensu. With regard to continuing education, there was broad adherence to the courses offered, with a preference for quarterly or semester courses, and a positive assessment of the relevance of these courses for the improvement of teaching practices. The study shows that intrinsic motivation, articulated with the offer of contextualized training programs, contributes significantly to the professional development of teachers and to the improvement of educational quality. Likewise, the findings underline the relevance of educational public policies that consider the profile, needs and interests of teachers, favoring effective continuous training opportunities in accordance with the contemporary demands of basic education.